Postangiographic 3D CT Findings of a Thrombosed Dissecting Aneurysm of the Posterior Inferior Cerebellar Artery - Sorimachi, Takatoshi (AJNR Am J Neuroradiol, 2004)
Summary: We report a case of a thrombosed dissecting aneurysm of the posterior inferior cerebellar artery with subarachnoid hemorrhage. Although the aneurysmal sac was not shown on an angiogram on the day of the onset, 3D CT performed immediately after angiography revealed the aneurysm. The patient was successfully treated by endovascular occlusion.